The Attitude of Iranian English Language Learners towards Web-Based Language Learning - Riasati, Mohammad Javad (LANGUAGE ART, 2024)
The rapid penetration of the Internet in various aspects of life, especially the aspects of education and learning, has made research in this field become an important and influential in the field of education. Therefore, the purpose of conducting this study with a mixed research method is to investigate the attitude of Iranian English language students towards web-based language learning. In this regard, 100 Iranian language learners participated in this research. Questionnaire of students’ attitude towards language learning through the Internet designed by Kia Hirati and Ahmadi Alashti (2015) and semi-structured interview were used as research tools. Descriptive statistical analysis method was used to analyze the data. In general, the obtained results showed that Iranian English language students have a positive attitude towards web-based language learning. The results of the interviews also confirmed the quantitative results of the research and showed that students believe that web-based learning can be an effective tool for learning English.